Equity Crowdfunding as an Alternative Modelization to SMEs and Investment Trends in Indonesia - Fathurrahman, Muhammad Iqbal; Fajri, Annisa; Purwanto, Edy (Economics and Business International Conference Proceeding, 2024)
The continuation of the business for UMKM is more important than the challenging filing processes at traditional banks, which might cause bankruptcy or make it difficult for some UMKM to launch a business. There is an alternative UMKM financing mechanism and an alternative investment option for investors called equity crowdfunding that integrates fund management services with information technology in the age of the industry 4.0 transformation towards society 5.0. As an alternate option for UMKM players to secure cash for the ongoing operations of their businesses, equity crowdfunding is now available on three platforms in Indonesia that are registered with and overseen by OJK. By regulating OJK, the Financial Services Authority plays a significant role in the upkeep and viability of the equity crowdfunding system. The government supervises and grants licenses to businesses that want to set up equity-based financial technologies. Regulations like OJK can present UMKM and alternative investment possibilities with opportunities.